Analisis Kerusakan Dan Tebal Lapis Tambah Perkerasan Lentur Ruas Jalan Piru-Loun Kabupaten Seram Bagian Barat - Franklin Tauran; David Daniel Marthin Huwae; Elisabeth Talakua (Universitas Pahlawan Tuanku Tambusai, 2024)
The Piru-Loun road section of West Seram Regency has a road width of 6m and a road length of 9.35km. The road damage that occurred was 4.35km long starting from STA 5+000 - 9+350. The damage that occurs is that the surface experiences deformation, grain release, cracks, and even holes, the potholes in the road have reached the pavement foundation layer and some even have visible subgrade layers. Technically, road damage indicates a condition where the road is structurally and functionally no longer able to provide optimal services for traffic activities. The aim of this research is to determine the damage and condition of the road, compare the thickness of the flexible pavement overlay and plan the budget (RAB). Damage analysis uses the Bina Marga method and in planning the thickness of the added layer (Overlay), the 1993 Aashto method and the 2017 Road Pavement Design Manual method, which are planning methods for determining the thickness of Indonesian standard pavement layers, the differences between the two flexible pavement methods (Flexible Pavement) will be shows which method is more efficient in application at the damage location. The results of the damage analysis show a priority order value of 5, included in the periodic maintenance program. The result of the added layer thickness using the 2017 Road Pavement Design Manual method was 2.5 cm and the 1993 Aashto method was 5.4 cm. The results of the analysis of the Cost Budget Plan for an added layer thickness of 5.4 cm amounted to IDR 973,858,542.62